ANALISIS NILAI DALAM CERITA RAKYAT SUKU TOLAKI PASAENO - Kiki Reski Wulandari (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2023)
This research aims to analyze the values in the folklore of the Tolaki tribe "Pasaeno". The method in this research is to use library research with a qualitative approach. Based on the results of the value analysis in the folklore of the Tolaki Pasaeno Tribe, several values were found contained in the folklore. Analysis of the values found are religious values, moral values and cultural values. The religious values contained in the text are religious values between fellow humans and their beliefs. Moral values are divided into two, namely moral values related to oneself, namely; hard work, honesty, courage and the value of patience. Moral values related to fellow humans are mutual respect between fellow humans and good prejudice between fellow humans. The cultural value contained is the value of love.